Efektivitas Pembelajaran PAK Dengan Metode NHT Berbantuan LKS Fase E SMA Theresiana 1 Semarang - Theresia Dua Rosa Nona Elsa; Anselmus Joko Prayitno; Andarweni Astuti (Concept: Journal of Social Humanities and Education, 2023)
Religious intolerance in Indonesia is quite high. In 2013 there were 245 violations of religious freedom. The attitude of intolerance found in the educational environment affects the learning outcomes of student. Research purposes: 1) To find out that learning using the LKS assisted NHT method has achieved completeness 2) to determine the effect of tolerance on the learning outcomes. 3) To find out changes in student learning achievement by applying the LKS assisted NHT method. Researchers used quantitative experimental research with the instruments: self-assessment questionnaires and knowledge tests. The results average score of tolerance assessment was 82.37 indicating that the LKS assisted NHT method was effective in increasing tolerance and PAK learning outcomes. The posttest score increased with a class average of 86.37. The regression test showed a positive effect of tolerance on learning achievement of 84%. The LKS assisted NHT method is effective in increasing PAK tolerance and learning achievement.